Associação entre a presença do polimorfismo dos genes IL6 (-174 G/C) e TGFβ1 (-509 T/C), a carga parasitária e o prognóstico em indivíduos com Leishmaniose visceral - Campelo, Cássio Marinho (2022)
Visceral leishmaniasis is a neglected parasitic anthropozoonosis with serious impacts on public health worldwide. Parasite-host interactions can a vital role in the host's immune response and disease outcome. The polymorphism gene for cytokine production is implicated in resistance or susceptibility in leishmaniasis. The present study aims to demonstrate the relationship between parasite load and genetic polymorphism of cytokine promoter genes IL-6 and TGF- β to the clinical prognosis of individuals with VL. Individuals diagnosed for VL seen at the São José Hospital for infectious diseases, aged 18 years and older, of both sexes, from the State of Ceará, were analyzed. Blood and marrow samples were analyzed using PCR RFLP and PCR- real time techniques. The results showed that 74 individuals, mostly men (86%), with a median age of 41 years, presented clinical and hematological characteristics typical of VL. The evaluation by clinical scores demonstrates for the prognosis of VL evolution, 33 patients were classified with worse prognosis and 41 with better prognosis. Coinfection with HIV affected 32 patients and of these 24 were classified as having a worse prognosis, mainly due to the low adherence to treatment, in addition to the occurrence of relapses in 7 patients. The detection of the parasite load of L. infantum was performed by the qPCR technique, being positive in 69 individuals and negative in 5 individuals. The parasite load was higher in the marrow than in the blood, with a mean of 4.70 x 104 Leishmanias/mL. no statistical differences related to the better or worse prognosis of VL, coinfection with HIV, and the presence of relapses were not presented. For the IL-6 gene (-174 G/C), the dominant frequency of the G allele (66%) and GG genotype (51%) was observed, not differing in the groups of patients with VL, coinfected or not with HIV, or how much to the prognosis of the disease. Individuals with the CC genotype have a higher parasite load in the bone marrow, with a median of 12.51 x 104 Leishmanias/mL. For the TGF-β1 gene (-509 C/T) a frequency of 56% of the C allele and 49% of the CT genotype was observed. In the distribution of genotypes according to disease prognosis, a frequency of 56.4% of the CT genotype was observed in individuals with a better prognosis and 45.8% of the CC genotype in individuals with a worse prognosis. However, no statistical difference was observed between the parasite load and the distribution of genotypes in the groups of patients, with and without HIV co-infection, and the prognosis of VL. The association of the CT genotype with the TT genotype showed a reduced risk (OR 0.17) in the development of severe forms of VL, suggesting that the higher frequency of the T allele in individuals with better prognosis and not coinfected with HIV is a protective factor in the disease . Parasitic tropism in the bone marrow triggers a series of immunological phenomena of multifactorial origin that may have repercussions on the effect of gene association, requiring a better understanding. The results showed that the presence of the polymorphism of the IL-6 (-174G/C) and TGF-β (-509 C/T) genes can contribute to the parasite load and the prognosis of VL.